A VIOLÊNCIAS DAS PALAVRAS NAS IMPRECAÇÕES JURÍDICAS - Candido, Maria Regina (PHOÎNIX, 2020)
The person in aniiguity who had suffered an injustice and had gone to the authorities in vain, had in fact only one authority at his disposal: the dafixiones, more commonly known as curse tablets. They are inscreved pieces of lead, usually in the form of small, thin sheets, intended to influence, by supernatural means, the actions or the welfare of persons